Risk analysis and assessment of information resoursces in fuzzy conditions - Казмірчук, Світлана Володимирівна (Ukrainian Information Security Research Journal, 2013)
The construction of information security management system requires providing the analysis and security risk assessment that are often characterized by high fuzzy conditions. The existing assessment tools do not provide opportunities for risk analysis and risk assessment of a wide range of initial parameters. On the basis of the proposed risk analysis and assessment method it was implemented an appropriate software system. It allows making assessment in fuzzy conditions using the established assessment components, which are displayed by the model of the integrated concept of risk parameters and can be represented in both numerical and linguistic forms. To verify the developed software product it was implemented the modeling under a number of different environmental conditions. The received results confirm the adequacy of software response on value changes of estimated component under different environment conditions, while the risk value does not change significantly when the basis of estimated components is changed.